The matador - Shepard, Richard; Brosnan, Pierce; Kinnear, Greg, 1963-; Davis, Hope, 1967-; Scott, Adam, 1973-; Dawson, Portia; Tattersall, David; Kent, Rolfe; Weinstein Company (Firm); Genius Products (Firm) ([Del Mar, CA] : Weinstein Company : Distributed by Genius Products, 2006)
Julian Noble is an unshaven, unnerved and unpredictable freelance assassin, who happens to encounter desperate businessman Danny Wright in the bar of a modern Mexico City hotel.
Originally released as a motion picture in 2005.
Special features: deleted scenes; feature commentary with director, Richard Shepard; commentary with Pierce Brosnan, Greg Kinnear & Richard Shepard; 'Making the Matador' featurette; 'The business & the treatment' : feature radio programs discuss The matador; TV commercial; theatrical trailer.
Director of photography, David Tattersall ; art directors, Marcelo Del Rio, Enrique Echeverr ;̕ editor, Carole Kravetz ; music, Rolfe Kent ; costume designer, Catherine Marie Thomas ; production designer, Robert Pearson.
Pierce Brosnan, Greg Kinnear, Hope Davis, Adam Scott, Portia Dawson, Roberto Sosa, Philip Baker Hall.
MPAA rating: R; for strong sexual content and language.
DVD. Dolby digital 5.1.
Keywords: Assassins -- Drama; Businessmen -- Colorado -- Denver -- Drama; Assassination -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Comedy films; Video recordings for the hearing impaired